Quantum electrodynamics in strong electromagnetic fields: substate resolved Kα transition energies in heliumlike uranium - Pfäfflein, Philip; Weber, G.; Allgeier, Steffen; Andelkovic, Z.; Bernitt, S.; Bondarev, A. I.; Borovik, A.; Duval, L.; Fleischmann, Andreas; Forstner, O.; Friedrich, M.; Glorius, J.; et al. (Physical review letters, 2025)
Using novel metallic magnetic calorimeter detectors at the CRYRINGESR, we recorded x-ray spectra of stored and electron cooled heliumlike uranium (U90+) with an unmatched spectral resolution of close to 90 eV. This allowed for an accurate determination of the energies of all four components of the K⁢𝛼 transitions in U90+. We find good agreement with state-of-the-art bound-state QED calculations for the strong-field regime. Our results do not support any systematic deviation between experiment and theory in heliumlike systems, the presence of which was subject of intense debates in recent years.